Beyond the Aesthetics: Understanding Risks in Nonsurgical Rhinoplasty - Czach, Magdalena; Kamińska, Monika Anna; Do, Monika Kienanh; Gonciarz, Marta Justyna; Paduszyńska, Natalia; Dąbrowska, Anna; Adamiec, Dominika Karolina; Strojny, Agnieszka Aleksandra; Zaliwska, Dominika; Kraszkiewicz, Adrianna; Czach, Zuzanna (Journal of Education, Health and Sport, 2024)
Nonsurgical rhinoplasty (NSR), colloquially referred to as a "liquid nose job," is a procedure that employs injectable fillers to modify the shape and contour of the nose. This procedure is particularly suited to patients presenting with minor imperfections and nasal defects. The procedure typically entails the injection of hyaluronic acid-based fillers, which are preferred due to their reversibility and safety profile. Although rare, dangerous complications are possible, therefore it is important to be aware of the risks associated with performing NSR and how to recognise and manage them. This article examines a number of potential complications associated with the procedure, including minor side effects such as bruising and swelling, as well as more serious risks such as vascular obstruction, skin necrosis and blindness. It is evident that the practitioner's experience and anatomical knowledge are of paramount importance in order to minimise the aforementioned risks. The aim of this review is to delineate the potential hazards associated with NSR. It is imperative that both clinicians and patients are cognizant that NSR is not a risk-free procedure. Dissemination of information may facilitate the implementation of safer practices and superior outcomes in facial aesthetic procedures.